EFFICIENT CONTROL OF HOUSEHOLD ELECTRICITY CONSUMPTION WITH WEMOS D1 MINI AND BLYNK IOT - Made adi surya antara; I Wayan Arsa Suteja; I Gede Eka Wiantara Putra Eka Wiantara Putra; Ida Bagus Putu Widja; Kadek Reda Setiawan Suda (Journal of Science and Engineering, 2026)
The electrical load monitoring system is a tool designed to monitor and measure electricity usage. The electrical load monitoring process uses a Wemos D1 Mini and PZEM004Tv30 model current and voltage sensor connected to an electrical load. The microcontroller used is the Wemos D1 Mini microcontroller which functions as the main control system that will be connected to a 16x2 LCD monitor with the aim of being monitored in real time and can be read directly on the LCD. By conducting experiments assembling the PZEM004Tv30 and Blynk IoT with the Wemos D1 Mini which produces a monitoring feature for power, energy, voltage, and current measurement readings. The result of this research is a household electricity measurement monitoring system that real times could monitoring anywhere through a prototype made using the Blynk IoT and PZEM004Tv30 sensor models with PZEM004Tv30 equipped with a 16x2 LCD to monitor the electrical energy load from household electronic devices in the form of current readings and equipped with a LCD 16x2 that displays when the load is detected the specified usage limit. The results of the error percentage test were obtained from the PZEM004Tv30 sensor measurement with the Wemos D1 Mini Microcontroller against the digital clamp meter. The ironing clothes load on the PZEM004Tv30 sensor measured current is 1.14 amperes while the measurement result on the Digital Clamp Meter is 1.12 Amperes. The error percentage of the PZEM004Tv30 against the digital clamp meter is 1.8%. The measurement results show that the prototype tool can be used as a current monitoring tool for electrical loads, with experiments using the PZEM004Tv30sensor being able to monitor properly and correctly the electricity usage and its usage capacity on household loads.